2005
DOI: 10.1080/13556210412331308976
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Studies of Psychostimulant-Induced Changes in Gene Expression

Abstract: Alterations in the expression of multiple genes in many brain regions are likely to contribute to psychostimulant-induced behaviours. Microarray technology provides a powerful tool for the simultaneous interrogation of gene expression levels of a large number of genes. Several recent experimental studies, reviewed here, demonstrate the power, limitations and progress of microarray technology in the field of psychostimulant addiction. These studies vary in the paradigms of cocaine or amphetamine administration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 95 publications
(151 reference statements)
6
54
0
Order By: Relevance
“…In this regard, Gsk-3a was differentially expressed in HR vs LR and has previously been reported to be downregulated after stimulant administration (Yuferov et al, 2005). The downregulation of Gsk-3a in HR but not LR ( Figure 5) could represent a compensatory adaptation to differences in these pathways in these two groups of rats.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this regard, Gsk-3a was differentially expressed in HR vs LR and has previously been reported to be downregulated after stimulant administration (Yuferov et al, 2005). The downregulation of Gsk-3a in HR but not LR ( Figure 5) could represent a compensatory adaptation to differences in these pathways in these two groups of rats.…”
Section: Discussionmentioning
confidence: 85%
“…Measurement of gene expression in rat brain provides a powerful means to address the molecular mechanisms underlying individual responsiveness to stimulants and there is a large literature on stimulant-induced gene expression changes in rodent brain (reviewed by Harlan and Garcia, 1998;Yuferov et al, 2005). However, for the most part, these studies have not addressed individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been suggested that a specific AMPA receptor subunit composition provides a fine-tuning in neuroadaptive processes derived from chronic drug exposure, including those that presumably control craving and relapse behavior (Lu et al, 2003;Tang et al, 2004;Yuferov et al, 2005). However, the contribution of different AMPA receptor subunits in this respect is less clear.…”
Section: Discussionmentioning
confidence: 93%
“…7,8,19 In addition to the cocaine-induced NAc plasticity, studies in rodent models indicate persistent or even permanent biochemical alterations in regions associated with the mesolimbic dopamine pathway including upregulation of the cyclic AMP (cAMP) pathway, [20][21][22][23][24][25][26] activator protein 1 family members [27][28][29][30][31][32] as well as glutamate, dopamine, gaminobutyric acid (GABA) and opiate receptors, growth factors, cytoskeletal elements and cell metabolism. [33][34][35][36][37][38][39][40][41] Genomic analyses in human post-mortem tissue of cocaine overdose (COD) victims have confirmed the findings of studies employing rodent models and have revealed novel mechanisms of drug-induced neuronal and non-neuronal dysregulation in human post-mortem brain tissue. [42][43][44][45] For example, Bannon and co-workers 42 examined gene expression in the NAc of post-mortem brain tissue of human cocaine abusers and controls and found significant alterations in several novel functional classes and transcripts including signal transduction, transcriptional and translational processing, neurotransmission and synaptic function, glia, structural and cell adhesion, receptors/transporters/ion channels, cell cycle and growth and lipid and protein processing.…”
Section: Introductionmentioning
confidence: 79%